2021
DOI: 10.3389/fcvm.2021.731730
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram to Predict the 180-Day Readmission Risk for Chronic Heart Failure: A Multicenter Prospective Study

Abstract: Background: The existing prediction models lack the generalized applicability for chronic heart failure (CHF) readmission. We aimed to develop and validate a widely applicable nomogram for the prediction of 180-day readmission to the patients.Methods: We prospectively enrolled 2,980 consecutive patients with CHF from two hospitals. A nomogram was created to predict 180-day readmission based on the selected variables. The patients were divided into three datasets for development, internal validation, and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…In Martin’s study, BUN was discovered to have a significant association with 28-day mortality ( 47 ), and Jamshid’s study identified BUN as one of the factors with the highest predictive values to predict the risk of mortality from patients with severe COVID-19 ( 48 ), which also provides support for our results. BUN was also identified as a significant variable for prolonged LOS and readmission prediction, and the same results can also be found in homogeneous studies ( 49 , 50 ). The increased level of BUN is associated with kidney damage, which is supported by multiple mechanisms ( 51 ).…”
Section: Discussionsupporting
confidence: 73%
“…In Martin’s study, BUN was discovered to have a significant association with 28-day mortality ( 47 ), and Jamshid’s study identified BUN as one of the factors with the highest predictive values to predict the risk of mortality from patients with severe COVID-19 ( 48 ), which also provides support for our results. BUN was also identified as a significant variable for prolonged LOS and readmission prediction, and the same results can also be found in homogeneous studies ( 49 , 50 ). The increased level of BUN is associated with kidney damage, which is supported by multiple mechanisms ( 51 ).…”
Section: Discussionsupporting
confidence: 73%
“…Readmission and death are the two most common adverse prognoses in patients with HF, and death is the most common outcome indicator in the current study; however, readmission has been shown in numerous studies to significantly increase the risk of death. [33][34][35][36] Therefore, we believe that the use of readmission as an outcome indicator complements previous studies by better confirming and building on findings from other HF cohort studies that malnutrition is a significant predictor of poor outcomes, readmission or death.…”
Section: Discussionsupporting
confidence: 76%
“…The findings of our study differ from those of most previous studies in that we included readmission as a primary outcome indicator, with the aim of exploring the impact of malnutrition on readmission in hospitalized patients with HF and screening for tools that could better predict readmission. Readmission and death are the two most common adverse prognoses in patients with HF, and death is the most common outcome indicator in the current study; however, readmission has been shown in numerous studies to significantly increase the risk of death 33–36 . Therefore, we believe that the use of readmission as an outcome indicator complements previous studies by better confirming and building on findings from other HF cohort studies that malnutrition is a significant predictor of poor outcomes, either readmission or death.…”
Section: Discussionsupporting
confidence: 75%
“…The continuous variables such as age (I: <60, II: 60–69, III: 70–79, IV: >79) and BMI (I:<18.5, II:18.5–24.9, III: 25–29.9, IV: >29.9) were transformed into categorical variables according to the criteria of studied documents 16 , 17 ; SBP, DBP, HR, BNP, LEVF, platelet count, neutrophil count, lymphocyte count, monocyte count, BUN, TG, TC, creatinine, HDL-C, LDL-C, Apolipoprotein-A, Apolipoprotein-B, and Lipoprotein(α) were transformed into categorical variables on basis of their corresponding best cut-off values. The properties of other parameters were unchanged.…”
Section: Methodsmentioning
confidence: 99%